2015
DOI: 10.1021/acs.jmedchem.5b00577
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of NCT-501, a Potent and Selective Theophylline-Based Inhibitor of Aldehyde Dehydrogenase 1A1 (ALDH1A1)

Abstract: Aldehyde dehydrogenases (ALDHs) metabolize reactive aldehydes and possess important physiological and toxicological functions in areas such as CNS, metabolic disorders, and cancers. Increased ALDH (e.g., ALDH1A1) gene expression and catalytic activity are vital biomarkers in a number of malignancies and cancer stem cells, highlighting the need for the identification and development of small molecule ALDH inhibitors. A new series of theophylline-based analogs as potent ALDH1A1 inhibitors is described. The optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…In vitro and in vivo studies in ovarian cancer have shown similar results wherein, siRNA-based ALDH1A1 targeting has sensitized the cells to Cisplatin/Taxol therapy and reduced tumor growth in xenograft models [44]. The use of the small molecule inhibitor, NCT-501, that specifically inhibits ALDH1A1 [27], provided similar results in this study. This molecule inhibited tumor burden in in vivo models and improved efficacy of Cisplatin in patient-derived ex vivo explant studies.…”
Section: Discussionsupporting
confidence: 77%
“…In vitro and in vivo studies in ovarian cancer have shown similar results wherein, siRNA-based ALDH1A1 targeting has sensitized the cells to Cisplatin/Taxol therapy and reduced tumor growth in xenograft models [44]. The use of the small molecule inhibitor, NCT-501, that specifically inhibits ALDH1A1 [27], provided similar results in this study. This molecule inhibited tumor burden in in vivo models and improved efficacy of Cisplatin in patient-derived ex vivo explant studies.…”
Section: Discussionsupporting
confidence: 77%
“…ALDH enzyme activity is a common marker of cancer stem cells in a variety of tissues and is associated with high tumor-initiating capacity of ovarian cancer cells and poor outcomes for patients with ovarian cancer (32,4749). Selective inhibitors of ALDH are in development and may provide a therapeutic benefit for tumor cells dependent on ALDH activity (42,48,50), particularly if used in combination with traditional chemotherapy. This study highlights how differential NF-κB signaling can maintain diverse phenotypes within the cancer spheroid.…”
Section: Discussionmentioning
confidence: 99%
“…NCT-501, which harbors a scaffold derived from caffeine, is a selective ALDH1 inhibitor. [66] It has been shown to be effective against patient-derived head and neck cancer cells, [67] where other conventional molecules were proven to be ineffective. The heterogeneous cell lines used in these studies had elevated levels of CD44, CD133 and ALDH1, indicating an increased CSC population in these tumors, which helps rationalize the susceptibility of these cells to NCT-501 treatment.…”
Section: Targeting the Metabolic State Of Cscs: Mitochondrial Metabolmentioning
confidence: 99%